Implementasi Algoritma Boyer-Moore Majority Vote pada Sistem Manajemen Inventory Berbasis Internet of Things - Lahama, Artquito Beltsazar; Sitanayah, Lanny; Pandelaki, Steven (Jurnal Pekommas, 2024)
Gold jewelry stores have to deal with various problems involving inventory control and inventory analytics in their day-to-day operations. Many Indonesian gold retailers tackle these problems by using a paperbased recording method. This method is not time efficient and adds more workload into the inventory management processes, such as stocktaking and popular item category classification. Stocktaking gets more difficult as more items are added to the inventory. These added workload and time increase the risk for items to go missing without being immediately documented. This paper proposes an Internet of Things solution that makes inventory stocktake more streamlined by introducing an RFID system with a web application that allows an operator to identify items during a stocktake instantly. In addition, store managers can also find trends in item categories using the Boyer-Moore majority vote algorithm. Our evaluation show that this system can effectively record data items in one scan with an average accuracy of 93.16% for a tray of 5 up to 25 items.